Sport skill level and gender with relation to age, physical development and special fitness of the participants of olympic volleyball tournament Beijing 2008 - Sterkowicz-Przybycien, K.; Sterkowicz, S.; Zak, S. (Collegium Antropologicum, 2014)
The aim of this study was to provide an answer to the question whether and how age, body height, body mass, body mass index and results from fitness tests are related to sport skill level and gender of the participants of the Olympic volleyball tournament. Two-Way ANOVA was used to find the dependency of the variables on the factor of sport skill level (A - teams which took places 1 to 4, B - places from 5 to 8; C - places from 9 to 12) and gender (F - female;M- male). Statistical significance was set at p<0.05. The Bonferroni's adjustment was carried out for three p=0.017 and fifteen p=0.003 pairs of comparisons). The M and F athletes included in A-C groups (N=48 in each group) were than compared to the classification in the neural network of Probabilistic Neural Network (PNN). A combined effect of the factors of sports level and gender on the height of attack jump (F=4.13; p=0.02) and block jump (F=9.22; p<0.001) was identified. The level of achievement was modified by the differences between the men and women. A significant advantage over the groups B and C was found for attack height and block height. In the group A, the differences between the results obtained for women and men in the ranges of attack and block with respect to the net height were not significant. Mean range of block jump did not match up to attack jump, particularly in women. The application of PNN network showed that age, BMI, relative attack jump and block jump are good predictors of sport results. The percentage of properly classified players in the group of men was lower than in women (42.4 vs. 56.3%). In this regard, big differences were found at the lower level of sport results: A (77.1 vs. 79.2%), B (25.0 vs. 25.0%) and C (25.0 vs. 64.6%). In conclusion, selection for national teams should take into consideration the players with long competitive experience with adequate weight/height ratios, who exhibit good training adaptations to jumping exercise.